CRB 8 Digital Vol. 5, n. 2 (2012) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
CRB 8 Digital Vol. 5, n. 2 (2012)Link de acesso ao númerohttp://revista.crb8.org.br/index.php/crb8digital/issue/view/10